2016
DOI: 10.5114/aoms.2016.57597
|View full text |Cite
|
Sign up to set email alerts
|

Flufenamic acid prevents behavioral manifestations of salicylate-induced tinnitus in the rat

Abstract: IntroductionTinnitus is defined as a phantom auditory sensation, the perception of sound in the absence of external acoustic stimulation. Given that flufenamic acid (FFA) blocks TRPM2 cation channels, resulting in reduced neuronal excitability, we aimed to investigate whether FFA suppresses the behavioral manifestation of sodium salicylate (SSA)-induced tinnitus in rats.Material and methodsTinnitus was evaluated using a conditioned lick suppression model of behavioral testing. Thirty-one Wistar rats, randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It suppresses the overall excitability of neurons by decreasing the spontaneous firing rate. In addition, TRPM7 is also an important regulator of cellular Zn 2+ which plays an antioxidant role under stressful conditions 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…It suppresses the overall excitability of neurons by decreasing the spontaneous firing rate. In addition, TRPM7 is also an important regulator of cellular Zn 2+ which plays an antioxidant role under stressful conditions 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-dependent cell death pathways are predominant in women [ 47 ], whereas oxidative stress-dependent activation and apoptosis inducing factor stimulation of poly (ADP-ribose) polymerase (PARP) are involved in men [ 48 , 49 ]. Bal et al [ 50 ] reported that inactivating TRPM2 ion channels would modulate the neuronal activity in the central audio path by reducing neural excitability, presumed to cause an increase in inhibitory signals in auditory nuclei leading to decreased tinnitus-producing signals. This suggests that a brain-protective mechanism against apoptosis in our menopausal group may work to prevent the apoptotic cascade by inhibiting TRPM2.…”
Section: Discussionmentioning
confidence: 99%
“…These features were earlier observed in response to aspirin and sodium salicylate, because salicylate was soon thought to be the active compound. Sodium salicylate-induced tinnitus is the most widely used animal model to study tinnitus in rats ( 1 3 , 38 ). In previous studies, BDNF was found to play a key role in the onset and the persistence of salicylate-induced tinnitus ( 39 ).…”
Section: Discussionmentioning
confidence: 99%